Social-Emotional Training for Aggressive Adolescents: Impacts on Attachment Styles, Social Desirability, and Emotional Regulation - Samadi Manaf, Mohammad Reza; Rahmani, Marjan; Dibazar Sadeghi, Azam (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to examine the effectiveness of a structured social-emotional training program in improving attachment styles, reducing social desirability tendencies, and enhancing emotional regulation in aggressive adolescents. Methods and Materials: A randomized controlled trial was conducted with 30 adolescents (aged 13–17) in Nigeria who exhibited elevated aggression levels. Participants were randomly assigned to either an experimental group (n = 15) that received an eight-session social-emotional training intervention or a control group (n = 15) that received no intervention. The sessions integrated elements of attachment theory, emotional self-regulation, and social skills training. Data were collected at pre-test, post-test, and five-month follow-up using standardized measures for secure, anxious, and avoidant attachment styles, social desirability, and emotional regulation. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests via SPSS-27. Findings: Statistically significant time × group interaction effects were found for all dependent variables (p < .001). The experimental group showed significant increases in secure attachment (F = 31.46, η² = .529) and emotional regulation (F = 32.07, η² = .540), and significant decreases in anxious attachment (F = 27.88, η² = .510), avoidant attachment (F = 29.33, η² = .515), and social desirability (F = 24.99, η² = .473). Post-hoc analyses confirmed significant changes from pre-test to post-test and follow-up in the experimental group for all outcomes, with no significant differences between post-test and follow-up, indicating sustained effects. Conclusion: The results demonstrate that targeted social-emotional training is an effective intervention for reducing maladaptive attachment patterns and social desirability behaviors while enhancing emotional regulation in aggressive adolescents. These findings support the integration of SEL-based programs into adolescent behavioral health services.